International Normalized Ratio Test Frequency in Left Ventricular Assist Device Patients Affects Anticoagulation Quality and Adverse Events. Issue 2 (February 2021) - Schlöglhofer, Thomas; Zapusek, Lydia; Wiedemann, Dominik; Riebandt, Julia; Wittmann, Franziska; Dimitrov, Kamen; Angleitner, Philipp; Haberl, Lisa; Laufer, Günther; Moscato, Francesco; Zimpfer, Daniel; Schima, Heinrich
Abstract : Anticoagulation therapy in patients using left ventricular assist device (LVAD) is essential to reduce hemocompatibility related adverse events (HRAEs). Vitamin K-antagonist dosage must be adapted and monitored by INR point-of-care testing (POCT) in outpatients. The study aims to determine if the frequency of INR POCT in LVAD outpatients has an influence on the quality of anticoagulation therapy (ACQ), HRAEs, and outcomes. This retrospective study included n = 48 patients who received LVAD implantation (HMII, HM3, and HVAD) between 2013 and 2017. ACQ (% of INR tests in range, PTR), outcomes and HRAEs using Kaplan–Meier curves were compared in a daily (n = 36) and 3×/week (n = 12) INR POCT group. Further, based on the achieved PTR ranging from 0–60% (poor), 61–70% (acceptable), and 71–100% (well controlled), HRAEs and outcomes were compared. Daily and 3×/week groups were similar in perioperative risk factors and INR target ( p = 0.28). Freedom from any HRAE (38.9% vs. 25.0%, p = 0.44), any readmission (72.2% vs. 75.0%, p = 0.97), and 1 year survival (91.7% vs. 91.7%, p = 0.98) were comparable in both groups. The PTR was significantly higher with the daily self-assessments (73.5% vs. 68.4%, p = 0.006). Well vs. poorly controlled INR POCT patients more often had ( p = 0.01) a daily POCT frequency (92%) vs. poorly controlled (54%) and significantly higher freedom from neurologic events (96.0 vs . 69.2%, p = 0.024) as well as hemorrhagic strokes (100% vs. 76.9%, p = 0.011). Well-controlled anticoagulation of LVAD outpatients is associated with less neurologic events. The frequency of INR POCT could be one of the key factors in the reduction of HRAEs, so future prospective, large-scale studies should help to clarify the effects.